Development of Self-Management Skills Measurement Model for Mathayomsuksa Students, Nakhonsawan Primary Education Service Area Office 3 - Jantarawong, Ekkawat; Nakaphong Asvaraksha, Nanthima (Suan Dusit Graduate School Academic Journal, 2025)
This research is a quantitative study with the following objectives: 1) To develop a self-management skill measurement scale for Mathayomsuksa students, which includes examining content and construct validity, discrimination power, and reliability; and 2) To develop normative criteria for self-management skills of Mathayomsuksa students. The sample group consists of 590 Mathayomsuksa students from the Nakhon Nayok Primary Educational Service Area Office 3, selected through multi-stage sampling. The instrument used is the self-management skill measurement scale for Mathayomsuksa students. The statistics used for data analysis include mean, standard deviation, percentiles, normalized T-scores, correlation coefficients, and confirmatory factor analysis, conducted using the Mplus program. The research findings are as follows: 1. The 36-item behavioral rating scale, with 5 levels of estimation, has an Item-Objective Congruence (IOC) ranging from 0.67 to 1.00, discrimination power ranging from 0.33 to 0.79, and reliability of 0.938. The construct validity is supported by the following fit indices: Chi-square = 476.602, df = 472, p-value = 0.4321, CFI = 0.998, TLI = 0.997, RMSEA = 0.009, and SRMR = 0.064.2. The local normative criteria for assessing self-management skills are divided into 5 levels : Very high: 164 points and above (≥T68), High: 139-163 points (T56-T67), Medium: 118-138 points (T44-T55), Low: 100-117 points (T32-T43) and Very low: below 99 points (<T31)